The Filipino bilingual from a scoiolinguistic perspective - Pascasio, Emy M. (2003)
A major feature of the Philippine language situation is its diversity. The Filipino bilingual lives in a multilingual and multicultural environment. The Filipino bilingual of today possesses a strong national identity but needs to seek to render it more functional for the purposes of national well-being in the modern world. Filipino rather than English can better serve as a medium to express the Filipino's cultural traditions, values, beliefs, and national aspirations. However, there are certain sociolinguistic realities that challenge the Filipino bilingual. One is that it is through bilingual education that we hope to equip the Filipino bilingual such that he/she will be better prepared to examine the nature of change in this modern world, including its speech and dimensions, and also to enable him/her to understand better the distinctions that must be made between change in the past and that which is on-going. His/her competence in English will equip him/her to handle modern technological developments and to keep up with the rapidity of technological change. The role of English maybe diminishing on the national level, but certainly for globalization and information technology, it is the language of wider communication in the international level. This paper will present the profile of the Filipino bilingual in terms of identity, sociolinguistic competencies including attitudes, motivations and proficiency within a multilingual and multicultural setting.
Includes bibliographical references (pages 77-79).